2017
DOI: 10.1038/s41598-017-04579-8
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase polymorphism is associated with the cortico-cerebellar functional connectivity of executive function in children with attention-deficit/hyperactivity disorder

Abstract: The cerebellum, although traditionally considered a motor structure, has been increasingly recognized to play a role in regulating executive function, the dysfunction of which is a factor in attention-deficit/hyperactivity disorder (ADHD). Additionally, catechol-O-methyltransferase (COMT) polymorphism has been reported to be associated with executive function. We examined whether the cortico-cerebellar executive function network is altered in children with ADHD and whether COMT polymorphism is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…In the current study, the results revealed that the DC values of the ADHD group were higher than normal controls in the bilateral middle cingulate gyrus. The cingulate gyrus is thought to play an important role in executive control (Mizuno et al (2017)). The middle cingulate gyrus is related to cognitive processing, such as the detection of errors or conflicts, as well as negative conditional reflexes and the prediction and awareness of pain.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the results revealed that the DC values of the ADHD group were higher than normal controls in the bilateral middle cingulate gyrus. The cingulate gyrus is thought to play an important role in executive control (Mizuno et al (2017)). The middle cingulate gyrus is related to cognitive processing, such as the detection of errors or conflicts, as well as negative conditional reflexes and the prediction and awareness of pain.…”
Section: Discussionmentioning
confidence: 99%
“…26, GE Healthcare, Milwaukee, WI, USA) with a standard head coil (8-channnel HD Brain, GE Healthcare). Resting-state functional images were acquired with a T2*-weighted gradient-echo echoplanar imaging (EPI) sequence 60,61 . Each volume consisted of 40 slices, with a thickness of 3.5 mm and a 0.5-mm gap, to cover the entire brain.…”
Section: Methodsmentioning
confidence: 99%
“…The field of view was 192 × 192 mm, and the matrix size was 64 × 64, yielding volume dimensions of 3 × 3 mm. A total of 192 volumes were acquired for an imaging time of 7 min 42 s 60,61 . The participants were instructed to remain awake but to close their eyes and think of nothing in particular.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations